2006
DOI: 10.3171/spi.2006.5.6.508
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of vascular anatomy for minilaparotomic anterior L4–5 procedures

Abstract: Careful preoperative evaluation of the vascular anatomy is essential to conducting successful anterior lumbar surgery. The determination of an appropriate approach can contribute to a reduction of unnecessary vascular retraction and a consequent decrease in vascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…As occurred in our cases, Kothbauer and Seiler reported transdural nerve root incarceration after microsurgical lumbar discectomy 5) . In 1994, Toppich et al reported complications similar to that case 9) .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As occurred in our cases, Kothbauer and Seiler reported transdural nerve root incarceration after microsurgical lumbar discectomy 5) . In 1994, Toppich et al reported complications similar to that case 9) .…”
Section: Discussionsupporting
confidence: 78%
“…These studies tell us that unrelieved trapped roots have a high possibility of incarcerating themselves in much the same manner that bowel loops are incarcerated in an abdominal wall hernia. The ischemic damage led to progressive pain and sensory motor deficit 5,9) ; however, no morbidity was associated with these events when the dura was adequately closed, primarily with sutures . Several investigators have reported the prevalence of unintended dural tears during lumbar spine surgery with variable incidences ranging from 1-17% 2,10) .…”
Section: Discussionmentioning
confidence: 99%
“…Our technique for the anterior approach has been described in detail elsewhere. 12 For single-and multilevel procedures, we used a left-sided, muscle-preserving technique, retracting the rectus muscle superolaterally. The peritoneal contents were placed rostrally using a robotic arm retractor, and vascular dissection was performed with dissecting swabs and a hand-held retractor.…”
Section: Surgical Techniquementioning
confidence: 99%
“…8 -11 Many researchers have already realized the importance of preoperative assessment of the prevertebral vascular structures and have studied the optimal trajectories to the spine that aid in the mobilization of major vessels and prevention of vascular injury. [12][13][14][15][16] Previous recommendations for optimal trajectories were generally based on the structural aspect of vascular mobilization. However, the tension in the vascular structure is also an important factor to be considered for adequate exposure of a target lesion.…”
mentioning
confidence: 99%